KORELASI SELF EFFICACY DENGAN PERILAKU MENYONTEK PADA SISWA - Devi, Ismalia Nadiya; Suyati, Tri; Dian, MA Primaningrum (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
Research on the relationship of self-efficacy with cheating behavior in students is motivated by that students often cheat during tests or exams. Many ways used by students to cheat include looking for answers on the internet, asking questions with friends and some opening small notes. The reason students cheat is because the material is poorly understood, unsure of their own answers so they ask friends, afraid of getting less than optimal results and learning with the speeding system overnight or even have not learned. This research is a type of quantitative research. Ex post facto research method with correlational approach. The population used in this study was students of SMA Negeri 2 Kendal class XI. What is used as a try out is class XI IPS 3. While the research samples were in class XI MIPA 1, XI MIPA 3, XI MIPA 4, XI IPS 1, XI IPS 2 and XI IPS 6. The sampling used is the cluster random sampling technique. This research data was obtained through the student self-efficacy scale and the student cheating behavior scale. The result of the correlation analysis between self-efficacy and student cheating behavior is that the relationship between self-efficacy and student cheating behavior of 0.729 is in a strong relationship so that it can be concluded that Self Efficacy with cheating behavior has a strong relationship. Based on the results of this study, suggestions that can be conveyed are to reduce student cheating behavior and BK teachers provide treatment or action. To be able to increase students' self-efficacy. Keywords: Self efficacy, Cheating Behavior